The Decisive Role of Mutual Arrangement of Hydroxy and Methoxy Groups in (3(4)-hydroxy-4(3)-methoxyphenyl)-4,7-dimethyl-3,4,4a,5,8,8ahexahydro- 2H-chromene-4,8-diols in their Biological Activity - Pavlova, Alla; Patrusheva, Oksana; Il'ina, Irina; Volcho, Konstantin; Tolstikova, Tat'yana; Salakhutdinov, Nariman (Letters in Drug Design & Discovery, 2017)
Background: The positional effects of the methoxy- and hydroxyl substituents in the phenyl ring were examined in vivo for distinct receptor classes in order to gain an insight into the mechanism by which isomeric compounds (2S,4R,4aR,8R,8aR)-2-(3(4)-hydroxy-4(3)-methoxyphenyl)-4,7-dimethyl- 3,4,4a,5,8, 8a-hexahydro-2H-chromene-4,8-diols 1 and 2 exhibit their pharmacological activity. Conclusion: Our findings suggest a strong structure-function relationship between the substitution pattern and the mechanism of biological activity of compound. The methoxy substituent at C4 and the hydroxyl substituent at C3 (compound 1) seem to employ the cannabinoid and adrenergic systems, whereas compound 2 with the methoxy substituent at C3 and the hydroxyl substituent at C4 possibly targets the opioid and dopaminergic mechanisms.
Keywords: dopaminergic system